Risk stratification and management of acute pulmonary embolism - Becattini, Cecilia (Hematology Am Soc Hematol Educ Program, 2016)
The clinical management of patients with acute pulmonary embolism is rapidly changing over the years. The widening spectrum of clinical management strategies for these patients requires effective tools for risk stratification. Patients at low risk for death could be candidates for home treatment or early discharge. Clinical models with high negative predictive value have been validated that could be used to select patients at low risk for death. In a major study and in several meta-analyses, thrombolysis in hemodynamically stable patients was associated with unacceptably high risk for major bleeding complications or intracranial hemorrhage. Thus, the presence of shock or sustained hypotension continues to be the criterion for the selection of candidates for thrombolytic treatment. Interventional procedures for early revascularization should be reserved to selected patients until further evidence is available. No clinical advantage is expected with the insertion of a vena cava filter in the acute-phase management of patients with acute pulmonary embolism. Direct oral anticoagulants used in fixed doses without laboratory monitoring showed similar efficacy (odds ratio [OR], 0.89; 95% confidence interval [CI], 0.70-1.12) and safety (OR, 0.89; 95% CI, 0.77-1.03) in comparison with conventional anticoagulation in patients with acute pulmonary embolism. Based on these results and on their practicality, direct oral anticoagulants are the agents of choice for the treatment of the majority of patients with acute pulmonary embolism.